Analisis Strategi Positioning Produk Berdasarkan Persepsi Konsumen Pada Industri Batik Di Jawa Timur - Kristiningsih Kristiningsih; Lestari Lestari; Wiwik Herawati (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2021)
Background - Competition in the Batik industry in Indonesia is quite sharp. Therefore it is necessary to apply the right marketing strategy in this industry. Whereas each batik industry that originates from the region has its own uniqueness that can attract the attention of consumers. Therefore, a positioning strategy for batik products is needed to be able to create more value in the minds of consumers compared to its competitors. Purpose - This research purposed to describe the position of competition (positioning) on batik industry in East Java based on the perceptions of local batik consumers. Design / Methodology / Approach - The study took samples of batik consumers in 9 cities in East Java, namely Bangkalan, Sidoarjo, Lamongan, Tuban, Pasuruan, Tulungagung, Mojokerto, Ponorogo and Banyuwangi. The population was taken by using purposive sampling technique. Respondents were taken as many as 200 respondents from selected batik producing cities. The research was conducted on 9 kinds of attributes that distinguish the distinctive characteristics of batik between regions in East Java including the quality of the fabric used, the quality of the coloring of the fabrics used, the patterns or motifs, the various colors, prices, design innovation, popularity, value art and intrinsic meaning. To conduct the analysis, analysis techniques using multidimensional scaling were used. Results and Discussion - The results showed a significant difference between the batik in each region which shows the characteristics of the area. The implication of this research was very useful for batik business in East Java to find out their competitive position among this industry in East Java, so that they can determine the right competition strategy according to the advantages or characteristics of each region. Conclusion - There are differences in perceptions of the quality attributes of the fabric material, the quality attributes of fabric coloring, batik patterns or motifs, various colors, prices, design innovation, popularity, artistic value and intrinsic meaning of batik batik in East Java which is the object of this research. Research implication - The research contributions are presented in the form of theoretical contributions and practical contributions. The theoretical contribution made is that this study supports previous research, that marketers can find out the competitive position in the industry through the perceived attributes of consumers. The implication of this research is very useful for marketers to find out who their close competitors are so that marketers can apply the right strategy to deal with competitors. Batik entrepreneurs or craftsmen should make products with high artistic value that characterize the Indonesian culture. Research limitations – The limitation of this study lies in the sample selection, because consumers only know the product attributes that they know, in the next research, consumer selection should preferably be on consumers who know all the characteristics of the businesses being compared. Further research can also examine the segmentation, targeting and positioning policies of batik products in marketing their products in the community.